First distribute the -3 and 7 into the parentheses:
-3x - 12 = 14x - 35
Now add 3x to both sides (to cancel the -3x):
-12 = 17x - 35
Then add 35 to both sides (to cancel the -35):
23 = 17x
Now divide both sides by 17 (to cancel the 17):
23/17 = x
That's your answer:
x = 23/17
or as a mixed fraction:
x = 1 6/17
2007-01-16 09:09:15
·
answer #1
·
answered by Puzzling 7
·
1⤊
0⤋
First multiply the one's in the bracket
-3(x+4)=7(2x-5) which equals
-3x-12=14x-35
then take the x's to the same side
-3x-14x=-35+12
-17x=-23 now divide both sides by by -17
x=23/17 is the answer or x=1.35
2007-01-16 17:14:11
·
answer #2
·
answered by TM 1
·
0⤊
0⤋
ok, step one is to distribute
-3(x+4) = -3(x)+-3(4) = -3x-12
7(2x-5) = 7(2x) + 7(-5) = 14x-35
ok so we have
-3x-12=14x-35
now we want to combine all our x's on oen side of the equation and the not x's on the other side
add 35 to both sides to get the numbers on the left, and add 3x to both sides to get the x's on the right so.........
23=17x
divide by 17
x= 23/17
hope this helps
matttlocke
2007-01-16 17:10:59
·
answer #3
·
answered by matttlocke 4
·
1⤊
0⤋
First: eliminate parenthesis > use distribution by multiply the outer terms with the terms in the parenthesis....
- 3(x) - 3(4) = 7(2x) - 7(5)
- 3x - 12 = 14x - 35
SEc: combine "like" terms > add 12 to both sides....
- 3x - 12 + 12 = 14x - 35 + 12
- 3x = 14x - 23
Third: subtract 14x from both sides...
- 3x - 14x = 14x - 14x - 23
-17x = - 23
*Solve for "x" by isolating it on one side > divide both sides by - 17
-17x/-17 = - 23/-17
x = 23/17
2007-01-16 17:14:03
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
-3(x+4) = 7(2x-5) (distribute the -3 and 7)
-3x-12 = 14x-35 (add 3x to both sides and add 35 to both sides)
23 = 17x
x = 23/17 = 1 6/17
2007-01-16 17:12:48
·
answer #5
·
answered by Rockit 5
·
1⤊
0⤋
-3(x+4) = 7(2x-5)
-3x - 12 = 14x - 35
-12 + 35 = 14x + 3x
23 = 17x
x = 23/17
2007-01-16 17:08:43
·
answer #6
·
answered by JasonM 7
·
2⤊
0⤋
x = 23/17
2007-01-16 17:16:50
·
answer #7
·
answered by sf_angelfish 1
·
0⤊
0⤋
Simplify both sides:
-3x-12=14x-35
You need your variables on one side so add 3x to both sides:
-12=17x-35
Add 35 to both sides:
23=17x
divide by 17:
23/17=x
2007-01-16 17:12:19
·
answer #8
·
answered by paulginallen 2
·
1⤊
0⤋
give me a break not doing our homework r we the big L for you
2007-01-16 17:15:26
·
answer #9
·
answered by high1315 2
·
0⤊
0⤋